CKD-Associated Complications : progress in the last half century - Nakanishi, Takeshi; Kuragano, Takahiro (Contributions to nephrology / series editor Claudio Ronco, 2019)
This publication is a record of some of the outstanding presentations given at the 63rd Annual Meeting of the Japanese Society for Dialysis Therapy (JSDT). The meeting was held in Kobe in 2018, celebrating the 50-year anniversary of the founding of the JSDT as a voluntary academic association. Therapy for end-stage kidney disease (ESKD) now faces vital issues besides the management of renal anemia and chronic kidney disease-mineral and bone disorder and the selection of the optimal treatment modality for each patient. These issues include the increasing incidence of malnutrition and frailty in the elderly, fragile vascular access, and the balance between medical costs and budgets. Expert members of the JSDT present 15 articles that address these issues. This book serves to promote further progress in understanding the pathogenesis of complications associated with ESKD and providing optimal therapy for patients.